Efektivitas Metode Sitz Bath Terhadap Intensitas Nyeri Luka Perineum Pada Ibu Postpartum di TPMB Mei Puji Lestari, Amd.Keb - Ayu Resky Mustafa; Robaini Robaini (Universitas Pahlawan Tuanku Tambusai, 2025)
90% of mothers experiencing perineal tears either spontaneously or due to episiotomy. Tearing in the perineum will cause pain which ultimately causes discomfort for the postpartum mother. One non-pharmacological method, namely hydrotherapy with a sitz bath, is a method used to reduce postpartum pain.To determine the effectiveness of the method Seat Bath on the intensity of perineal wound pain in postpartum mothers at TPMB May Puji Lestari, Amd.Keb in 2024.Use quasi experiment and approach one group pre-post test design. The research population was 60 mothers giving birth. The research sample used the Slovin formula which obtained a sample size of 38 respondents. Bivariate analysis uses tests Wilcoxcon. The research instrument used a questionnaire sheet and research observation sheet.Test results Wilcoxone Signed Test The obtained p value = 0.000 <0.05 so it can be concluded that there is an influence on the effectiveness of the method seat bath on the intensity of perineal wound pain in postpartum mothers at TPMB Mei Puji Lestari, Amd.Keb.There is an influence on the effectiveness of the method Seat Bath Regarding the Intensity of Perineal Wound Pain in Postpartum Mothers at TPMB May Puji Lestari, Amd.Keb 2024. This research can be used as reading material as a source of knowledge for the community and as a reference for the community in applying the sitz bath method as an effort to relieve post Sectio Caesarea pain in oneself , family or relatives.